UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DI KELAS IV SD NEGERI 091621 PERDAGANGAN - Des Alvani Lovenia Harefa; Ester Julinda Simarmata; Antonius Remigius Abi; Darinda Sofia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses whether applying Think-Pair-Share cooperative learning model can improve students’ learning outcomes on the theme of ‘the place where I live’ for fourth-grade students of SD Negeri 091621 Perdagangan in the academic year 2021/2022. The subjects involved 33 fourth-grade students, which consisted of 16 male and 17 female students. Type of the research was Classroom Action Research, which included four stages of planning, implementation, observation, and reflection. Data collection techniques used were observation and tests. It is seen from the research results conducted in the pretest, students who achieved a standard score were 6 students or 18% with an average score of 45. In addition, in the first cycle, students who achieved a standard score were 16 students or 48%. Meanwhile, students who did not achieve the standard score were 17 students or 52%. Thus, there was an increased score in the first cycle that was compared to the pretest. In fact, it did not achieve a qualified completeness category. Hence, in cycle II, students who achieved a standard score were 29 students or 88%. Whilst students who did not achieve the standard score were 4 students or 12%. Clearly, there was an improvement in cycle II that was compared to cycle I and it achieved a qualified completeness category.